(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2022)
This study aimed to describe the participant’s responses to implementing online lectures and various accompanying aspects. The research method chosen is a qualitative descriptive method. The research participants comprised 85 fifth-semester students at a tertiary institution in Indonesia who had attended online lectures and used the Learning Management System (LMS) service. Identification, clarification, reduction, analysis, and description techniques were carried out to process data from questionnaires and interviews to answer the problems under study. The study results show that participants in online lectures prefer the zoom meeting platform for synchronous lecture types. With the recording facility, participants can re-learn through the LMS application in the video link feature. However, participants prefer the WhatsApp application to discuss their problems. The biggest obstacle they face in online lectures is the stability of the internet network, even though most of them have internet access on a subscription basis. The weakness of online lectures is the lack of interaction, the hope of participants after the pandemic is over is the implementation of blended lectures with the distribution of lecture components in online and offline sessions.